Strategi Belajar Bahasa Indonesia Siswa SMA Di Kota Padang Dalam Penerapan Kurikulum Merdeka - Putri, Reza; Ramadhanti, Dina; Mana, Lira Hayu Afdetis (Universitas Muhammadiyah Jember, 2023)
This study aims to describe the types of learning strategies used by students in learning language. Differentiated based on direct strategies (cognitive strategies, memory strategies, and completion strategies) and indirect strategies (metacognitive strategies, affective strategies, and social strategies). This type of research is in the form of quantitative and survey methods. A total of 272 high school students in the city of Padang were given questionnaires to collect strategies used by students in learning Indonesian. Data analysis techniques using descriptive and factor analysis. Descriptive analysis to calculate the percentage of learning strategies used by students. Factor analysis is used to determine the most dominant strategy used by students. The results of the data analysis showed that the students used the most dominant cognitive strategy. The independent curriculum encourages students to develop critical and creative thinking skills. The results of the study show that students from the same city as Padang use direct and indirect strategies. Students use cognitive strategies 80.2%. Students use 83% memory. Students use the 85% recovery strategy. Students use metacognitive strategies 82.1%. Students use affective strategies 86.4%. Students use social strategies 83%. After the factor test was carried out, it was found that the most dominant strategy was used by cognitive students, namely. In implementing the independent curriculum at Padang City High School specifically in learning Indonesian. Cognitive strategies used by students to respond to the pedagogical genre used by the teacher. Students use cognitive strategies, construct contexts, write together and independently